N-aryl-piperidine-4-carboxamides as a novel class of potent inhibitors of MALT1 proteolytic activity. Issue 12 (1st July 2018) - Schlapbach, Achim; Revesz, Laszlo; Pissot Soldermann, Carole; Zoller, Thomas; Régnier, Catherine H.; Bornancin, Frédéric; Radimerski, Thomas; Blank, Jutta; Schuffenhauer, Ansgar; Renatus, Martin; Erbel, Paulus; Melkko, Samu; et al.
Graphical abstract: Highlights: MALT1 plays a key role in NF-κB pathway activation. A weak hit was optimized to potent and selective inhibitors of the MALT1. Compounds show activity in several mechanistic cellular assays. A good in vitro - in vivo correlation was established using a rat hepatocyte assay. Abstract: Starting from a weak screening hit, potent and selective inhibitors of the MALT1 protease function were elaborated. Advanced compounds displayed high potency in biochemical and cellular assays. Compounds showed activity in a mechanistic Jurkat T cell activation assay as well as in the B-cell lymphoma line OCI-Ly3, which suggests potential use of MALT1 inhibitors in the treatment of autoimmune diseases as well as B-cell lymphomas with a dysregulated NF-κB pathway. Initially, rat pharmacokinetic properties of this compound series were dominated by very high clearance which could be linked to amide cleavage. Using a rat hepatocyte assay a good in vitro - in vivo correlation could be established which led to the identification of compounds with improved PK properties.